(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Elastography in breast cancer cases has not become a routine examination that is conducted in the radiodiagnostic unit in Dr. Soetomo Teaching Hospital Surabaya. These last few years, elastography has been an addition examination modality which is promising to assess breast lesions that are detected byan ultrasound. Objective: The aim of the present study is to observe the performance of elastography in breast tumor cases. Method: This cross-sectional study was conducted in Dr. Soetomo Teaching Hospital Surabaya. The elastography is applied in 65 females (the average age is 49,1 years old) and it was found 66 lesions with a definitive diagnosis (34 benign tumors, 32 malignant tumors) which was proved through a fine-needle aspiration biopsy. The grayscale result is classified into benign and malignant categorizations with examining five descriptors including shape, margin, orientation, echo pattern, and posterior features. Results: The elastography score showed that the sensitivity is 87,5 %, the specificity is 94,1 %, and the accuracy is 90,9 % The stain ratio showed 93,8 %, 94,1 %, 90,9 % in sequence. On the other hand, the grayscale result showed 96,9 %, 91,2 %, and 95,5 %. The combination of elastography and grayscale showed a better performancewith the 97,1% of sensitivity, 94,1 % of specificity, and 93,8 % of accuracy. There was a significant correlation between the lesion size and the quality of elastography result (P = .034) while there was no correlation with the lesion depth (P = .624). Conslusion: The combination of elastography and grayscale have a better diagnostic performance in distinguishing benign breast tumor with malignant breast tumor.